2010
DOI: 10.1016/j.stem.2010.07.010
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Basal-like Breast Cancers Originate from Luminal Epithelial Progenitors and Not from Basal Stem Cells

Abstract: Breast cancers in BRCA1 mutation carriers frequently have a distinctive basal-like phenotype. It has been suggested that this results from an origin in basal breast epithelial stem cells. Here, we demonstrate that deleting Brca1 in mouse mammary epithelial luminal progenitors produces tumors that phenocopy human BRCA1 breast cancers. They also resemble the majority of sporadic basal-like breast tumors. However, directing Brca1 deficiency to basal cells generates tumors that express molecular markers of basal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
670
5
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 684 publications
(762 citation statements)
references
References 48 publications
50
670
5
7
Order By: Relevance
“…Within the basal population, a CD24 þ /Low Sca-1 À CD49f Low population (previously identified as mainly myoepithelial cells) and a CD24 þ /Low Sca-1 À CD49f High population (previously shown to be highly enriched for mammary stem cells) could be recognised Sleeman et al, 2007). Within the luminal population, CD24 þ /High Sca-1 À luminal cells (mainly ER À progenitors) and CD24 þ /High Sca-1 þ luminal cells (mainly differentiated ER þ cells) could be distinguished ( Figure 1a and Supplementary Figure 1) (Sleeman et al, 2007;Molyneux et al, 2010).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Within the basal population, a CD24 þ /Low Sca-1 À CD49f Low population (previously identified as mainly myoepithelial cells) and a CD24 þ /Low Sca-1 À CD49f High population (previously shown to be highly enriched for mammary stem cells) could be recognised Sleeman et al, 2007). Within the luminal population, CD24 þ /High Sca-1 À luminal cells (mainly ER À progenitors) and CD24 þ /High Sca-1 þ luminal cells (mainly differentiated ER þ cells) could be distinguished ( Figure 1a and Supplementary Figure 1) (Sleeman et al, 2007;Molyneux et al, 2010).…”
Section: Resultsmentioning
confidence: 81%
“…Using functional assays, we show that c-Kit expression marks progenitors with high in vitro proliferative potential, but that the majority of mammary stem cells (MaSCs) are c-Kit À . We demonstrate that in a mouse model of Brca1 breast cancer that phenocopies the human disease (Molyneux et al, 2010), the tumours express Kit and its downstream effector Lyn at levels comparable to those luminal ER À progenitors, which are most strongly c-Kit þ . Importantly, we demonstrate that c-Kit is required for mammary epithelial cell survival.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…5,14 This has been emphasized in a recent study, which suggested that at least a subgroup of basal-like breast cancers may originate from luminal progenitors rather than basal/ myoepithelial cells of the breast, 57 and confirmed by the results of conditional mouse models. 58 In this context, it is important to note that histogenesis and differentiation are two distinct processes although often mistakenly used as synonyms. Basal-like and triple-negative breast cancers…”
Section: What Is a Basal-like Breast Cancer?mentioning
confidence: 99%